Advances in the Science and Engineering of Casting Solidification An MPMD Symposium Honoring Doru Michael Stefanescu - Nastac, Laurentiu; Liu, Baicheng; Fredriksson, Hasse; Lacaze, Jacques; Hong, Chun-Pyo; Catalina, Adrian; Buhrig-Polaczek, Andreas; Monroe, Charles; Sabau, Adrian; Elena Ligia Ruxanda, Roxana; Luo, Alan; Sen, Subhayu; et al. (The Minerals, Metals & Materials Series, 2016)
This collection encompasses the following four areas: (1) Solidification processing: theoretical and experimental investigations of solidification processes including castings solidification, directional solidification of alloys, electromagnetic stirring, ultrasonic cavitation, mechanical vibration, active cooling and heating, powder bed-electron beam melting additive manufacturing, etc. for processing of metals, polymers and composite materials; (2) Microstructure Evolution: theoretical and experimental studies related to microstructure evolution of materials including prediction of solidification-related defects and particle pushing/engulfment aspects; (3) Novel Casting and Molding Processes: modeling and experimental aspects including high pressure die casting, permanent casting, centrifugal casting, low pressure casting, 3D silica sand mold printing, etc.; and (4) Cast Iron: all aspects related to cast iron characterization, computational and analytical modeling, and processing.